Development of a Canva-Based Interactive E-Module Using Problem-Based Learning on Human Reproductive System Material - Setiani, Yusnaida Eka; Warpala, I Wayan Sukra; Heny, Ajeng Purnama (SEARCH: Science Education Research Journal, 2026)
The research on the development of an Interactive E-Module based on PBL on human reproductive system material for grade XI high school students aims to develop a more interactive learning medium, one of which is through the E-Module, in order to facilitate the teaching and learning process independently and flexibly. This research aims to develop an Interactive E-Module based on PBL on the material of the human reproductive system for grade XI high school that is valid and practical, which can be used as teaching material in the Merdeka Curriculum. The specific purpose of this research is to determine the design, practicality, and validity of the E-Module media. The research method used was the ASSURE development research model. The research location is at SMA Negeri 3 Singaraja. Validity testing using Likert scale calculations with 2 material experts and 2 media experts. From the two experts, the validity level values of the material experts and media experts were obtained at 90.38%, this categorized as highly valid. The practicality test was carried out by 3 students in individual trials and 12 students in small group trials with different cognitive abilities. From the individual test results, the study obtained a score of 92%, while the small group trial obtained a result of 86.1% in the highly practical. It can be concluded that the development of an Interactive E-Module based on PBL on the human reproductive system material is highly valid and highly practical to be used as teaching material for phase F at SMA Negeri 3 Singaraja.